2019
DOI: 10.1136/bmj.l1652
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk in transgender people receiving hormone treatment: nationwide cohort study in the Netherlands

Abstract: ObjectiveTo investigate the incidence and characteristics of breast cancer in transgender people in the Netherlands compared with the general Dutch population.DesignRetrospective, nationwide cohort study.SettingSpecialised tertiary gender clinic in Amsterdam, the Netherlands.Participants2260 adult trans women (male sex assigned at birth, female gender identity) and 1229 adult trans men (female sex assigned at birth, male gender identity) who received gender affirming hormone treatment.Main outcome measuresInci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
302
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(316 citation statements)
references
References 30 publications
4
302
0
10
Order By: Relevance
“…Albeit studies remain scarce, the same discrepancy is observed for transgender male to female, where breast cancer is usually diagnosed at a younger age 51.5-year old while the incidence of breast cancer is increased by 46-fold when compared to male [13 , 14] . The transition from male to female relies on antiandrogens and estrogen therapies, which increase the risk of breast cancer [14] .…”
Section: Incidence Of Breast Cancersmentioning
confidence: 96%
“…Albeit studies remain scarce, the same discrepancy is observed for transgender male to female, where breast cancer is usually diagnosed at a younger age 51.5-year old while the incidence of breast cancer is increased by 46-fold when compared to male [13 , 14] . The transition from male to female relies on antiandrogens and estrogen therapies, which increase the risk of breast cancer [14] .…”
Section: Incidence Of Breast Cancersmentioning
confidence: 96%
“…The research included 2260 transgender women and 1229 transgender men receiving gender‐affirming hormones at the VU University Medical Center Amsterdam's gender clinic. The study concluded that the breast cancer risk for the transgender women, who received mostly antiandrogen and estrogen therapy, was approximately 47‐fold higher than the risk for Dutch cisgender men, but more than 3‐fold lower than the risk for Dutch cisgender women . The risk for transgender men receiving testosterone therapy likewise was much higher than that for cisgender men but approximately 5‐fold lower than the risk for cisgender women.…”
Section: An Uncertain Riskmentioning
confidence: 98%
“…5 Breast cancer risks for transgender women with longitudinal exposure to estrogen are reported to be greater than cisgender women but less than cisgender men. 6 Cervical cancer risks for transgender men are sometimes erroneously assumed by providers to be lower than for cisgender women. 7 Cancers are most treatable when cancer screening is guideline driven.…”
Section: Introductionmentioning
confidence: 99%